(untitled) (Journal Of Educational and Psychological Researches, 2011)
Autism is considered as one of the most developmental problems in the world that interfere with children growth and affect their social ,emotional and cognitive development child with autism used to be normal in his growth but in his development parents started to notice that their child characterize by loneliness and withdrawal himself from the surrounding world with some mannerism behaviors these characteristics used to be manifested children during the 1st three year of their life . It appears, one in every 500 birth (The American International Institution for child health 1997. and it would be less in females than makes at 1/4 percent . Aim is to build the autism scale for children , and the total population of (Rami,AL-amal,AL-saadah) institutes for handicapped in Baghdad were 447 children (boys and girls) (400)children (boys and girls ) were chosen randomly to fulfill the requirement of the study, children were from3-13 years old at academic year 2006/2007 . 210 of them Males and 237 females. (18) teachers from the above institutes chosen to apply ,. The scale to be applied for autistic children is consist of five elements ,1st element is (language and communication is weighted 27% , 2nd element is visual understanding of the child weight 13% ,3rd element is social adaptation of the child that weight 20%,4th is effervescence behavior weight 20% , and finally the 5th element which is gross and fine motor skill assessment that weight 20%, ). and it has been (90) items were formulated and then (10) of the formulated items were omitted and only (80) items were discovered to be reliability and validity , Pearson correlation coefficient while the scale reliability has been done in two ways ( test Re test , Alfa Cronbach) were used to analyze the result. and the standard error of the scale has been extracted which leads for some recommendation and suggestions of them is to benefit of the research indigenizing autism children in primary schools .